Multi-centre, multi-vendor reproducibility of 7T QSM and R2* in the human brain: Results from the UK7T study - Rua, C; Clarke, WT; Driver, ID; Mougin, O; Morgan, AT; Clare, S; Francis, S; Muir, KW; Wise, RG; Carpenter, TA; Williams, GB; Rowe, JB; et al. (Elsevier, 2020)
Introduction: We present the reliability of ultra-high field T2* MRI at 7T, as part of the UK7T Network's “Travelling Heads” study. T2*-weighted MRI images can be processed to produce quantitative susceptibility maps (QSM) and R2* maps. These reflect iron and myelin concentrations, which are altered in many pathophysiological processes. The relaxation parameters of human brain tissue are such that R2* mapping and QSM show particularly strong gains in contrast-to-noise ratio at ultra-high field (7T) vs clinical field strengths (1.5–3T). We aimed to determine the inter-subject and inter-site reproducibility of QSM and R2* mapping at 7T, in readiness for future multi-site clinical studies.